THE IMPACT OF MINIMUM WAGE POLICY ON HUMAN CAPITAL MANAGEMENT AND ECONOMIC PERFORMANCE - Adrie Charviandi; Mohammad Ahmad Bani Amer (CV. Adiba Aisha Amira, 2024)
This study examines the impact of minimum wage policies on human resource management (HRM) and economic performance. By using the literature analysis method. The results show that the minimum wage policy encourages companies to optimise the use of labour, increase productivity, and invest in employee skills development. However, its impact on economic performance is complex, with the potential for increased consumer purchasing power accompanied by the risk of inflation and reduced employment. The study concludes that effective minimum wage policy implementation requires a balanced and adaptive approach, taking into account local economic conditions and diverse industry needs.